2009
DOI: 10.1103/physrevc.80.065201
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected impact ofDwaves in low-energy neutral pion photoproduction from the proton and the extraction of multipoles

Abstract: Contributions of D waves to physical observables for neutral pion photoproduction from the proton in the near-threshold region are studied and means to isolate them are proposed. Various approaches to describe the multipoles are employed-a phenomenological one, a unitary one, and heavy baryon chiral perturbation theory. The results of these approaches are compared and found to yield essentially the same answers. D waves are seen to enter together with S waves in a way that any means which attempt to obtain the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(77 citation statements)
references
References 46 publications
4
73
0
Order By: Relevance
“…5. The possible importance of d-wave amplitudes in the photon asymmetry was pointed out in [29] recently. Within our scheme we have no freedom to significantly increase the asymmetry without destroying the successful description of the photoproduction multipoles at higher energies.…”
Section: Resultsmentioning
confidence: 99%
“…5. The possible importance of d-wave amplitudes in the photon asymmetry was pointed out in [29] recently. Within our scheme we have no freedom to significantly increase the asymmetry without destroying the successful description of the photoproduction multipoles at higher energies.…”
Section: Resultsmentioning
confidence: 99%
“…So far we are yet to see any significant change between the three calculations so it appears that D-waves do not play a significant role. This might change with data on other observables more sensitive to higher order partial waves [3].…”
Section: Pos(cd15)072mentioning
confidence: 99%
“…They concluded that both theories fail to describe the process beyond energies of E γ ≈ 170 MeV. Two explanations have been suggested for these failures: the need for the ∆(1232) to be included as a degree of freedom; and the possibility that D-waves (or higher) have a greater impact on observables than expected [3]. It should not come as a surprise that the ∆(1232) is required when studying photoproduction well beyond threshold, as the mass difference between it and the nucleon is not large,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore give only a rough estimate of this uncertainty. The extractions of the proton S-wave photoproduction amplitude based on CHPT using various approximations [24] lead to an uncertainty ∆E π 0 p 0+ ≈ ±0.05 × 10 −3 /M π + , which is about 5%. The uncertainty of the neutron S-wave threshold amplitude is estimated to be the same.…”
Section: Single Nucleon and Leading Two-nucleon Contributions At Thrementioning
confidence: 99%